Breastfeeding Knowledge and Colostrum Provision at South Tapanuli Regional Hospital - Siregar, Rya Anastasya; Batubara, Novita Sari; Heriansyah, Rizka; Lubis, Tapi Endang Fauziah (International Journal of Public Health Excellence (IJPHE), 2024)
Colostrum is needed by newborns as an early nutrient that affects the development and growth of babies, besides colostrum also plays a role in the initial formation of the baby's immune system. The purpose of this study was to determine the relationship between the level of knowledge of breastfeeding mothers and the provision of first breast milk (colostrum) in the midwifery room at the South Tapanuli District Hospital in 2022. The sample in this study amounted to 45 people with total sampling technique. Data analysis used univariate and bivariate. The results showed that there was a significant relationship between knowledge of breastfeeding mothers and the provision of first breast milk (colostrum) in the obstetrics room of the South Tapanuli District Hospital as indicated by the Spearman correlation test value, the value of = 0.000 was obtained. The results of this study are to increase the knowledge of breastfeeding mothers about the first breastfeeding (colostrum).